Research and development investment of Chinese chemical pharmaceutical companies under the national pooled procurement: a retrospective panel data analysis, 2013–2022 - Yuanli Liu; Jing Sun; Qianrun Lei; Qiyou Wu; Zhitao Wang (BMJ Open)
Objective To generate evidence about changes in the research and development (R&D) investment of Chinese chemical pharmaceutical companies before and after the implementation of the national pooled procurement, to respond to the concerns that significant price reductions might negatively affect R&D investment, and to facilitate the evidence-based decision-making for improvement of the national pooled procurement.Methods This retrospective study employed the fixed-effects models with robust SEs to analyse the changes in R&D investment intensities of 76 A-share listed Chinese chemical pharmaceutical companies before and after the procurement implementation in 2019. The analyses were based on a panel data set between 2013 and 2022. Subgroup analyses were conducted to account for the heterogeneity of the target companies. The bootstrap hypothesis test method was employed to assess potential variations across the different subgroups.Results Following the procurement implementation, the R&D investment intensity (RDI) of the target companies increased by 1.9% (p<0.05) compared with the RDI before the procurement implementation. Successful bidders exhibited a higher RDI of 2.2% (p<0.01) compared with that of the other suppliers. The RDI of companies engaged in traditional Chinese medicine (TCM) production was found to be 2.4% lower (p<0.01) than that of companies not involved in TCM production. Similarly, the companies engaged in the production of active pharmaceutical ingredients (APIs) had a 1.6% lower (p<0.01) RDI than those not involved in API production.Conclusions This study found that the enthusiasm of Chinese chemical medicines companies towards investing in R&D following the medicines regulatory reforms was not suppressed when the pilot pooled procurement was expanded and continued. The overall level of RDI following the pilot was higher than that before the pilot during the entire observation period. The enhanced investment in R&D has been a distinctive feature of Chinese chemical pharmaceutical companies that position themselves with more substantial market competitiveness.